1999
DOI: 10.1002/hep.510300510
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trials inHepatology: Predictors of quality

Abstract: Evidence shows that the quality of randomized clinical trials (RCTs) affects estimates of intervention efficacy, which is significantly exaggerated in low-quality trials. The present study examines the quality of all 235 RCTs published in HEPATOLOGY from the initiation in 1981 through August 1998. Quality was assessed by means of a validated 5-point scale and separate quality components associated with empirical evidence of bias. Only 26% of all RCTs reported sample size calculations, 52% adequate generation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
71
2

Year Published

1999
1999
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(77 citation statements)
references
References 40 publications
(83 reference statements)
4
71
2
Order By: Relevance
“…Several studies have demonstrated that small clinical trials are more susceptible to bias, are often less methodologically rigorous, and produce relatively less precise estimates of the true effect of treatment than large, multicenter studies. [34][35][36] Our results are important because the use of alternative medicines in general, and omega-3 free fatty acid formulations in particular, is widespread among patients with inflammatory bowel disease. [37][38][39][40][41] This may be due, in part, to dissemination of the positive results obtained in the trial by Belluzzi et al Given the negative results observed in the EPIC trials and in the trial by Lorenz-Meyer et al, 22 we do not endorse this practice, since patients with Crohn disease who are at risk for relapse would be better served by taking medications of known efficacy.…”
Section: Commentmentioning
confidence: 90%
“…Several studies have demonstrated that small clinical trials are more susceptible to bias, are often less methodologically rigorous, and produce relatively less precise estimates of the true effect of treatment than large, multicenter studies. [34][35][36] Our results are important because the use of alternative medicines in general, and omega-3 free fatty acid formulations in particular, is widespread among patients with inflammatory bowel disease. [37][38][39][40][41] This may be due, in part, to dissemination of the positive results obtained in the trial by Belluzzi et al Given the negative results observed in the EPIC trials and in the trial by Lorenz-Meyer et al, 22 we do not endorse this practice, since patients with Crohn disease who are at risk for relapse would be better served by taking medications of known efficacy.…”
Section: Commentmentioning
confidence: 90%
“…Five analyses reported that industry-sponsored studies were of comparable quality to nonindustry-sponsored studies 40,41,[50][51][52] ( 53,54 found that RCTs published in industry-sponsored supplements were generally of lower quality compared with RCTs published in parent journals. These findings were ascribed to a difference in peer-review process between industrysponsored supplements and parent journals.…”
Section: Financial Conflicts Of Interest In Biomedical Researchmentioning
confidence: 96%
“…Articles published in symposia were also similar in quality to those published in the parent journal, although articles published in symposia sponsored by a drug company compared with other symposia articles were less likely to contain a methods section that enabled readers to critically evaluate a study. Finally, a study that assessed the quality of 235 RCTs published in Hepatology from 1981 through 1998 found that higher quality trials were more likely to be sponsored by public organizations (OR=4.2) or by drug or device companies (OR=4.7) than not, although the overall quality of trials in the study was only moderate (i.e., mean of 3 on a validated 5-point scale) (Kjaergard et al 1999).…”
Section: Influences Of Conflicts Of Interest On Behaviormentioning
confidence: 98%